Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Following carbon condensation by in situ TEM: towards a rational understanding of the processes in the synthesis of nitrogen-doped carbonaceous materials - Piankova, Diana; Kossmann, Janina; Zschiesche, Hannes; Antonietti, Markus; Lopez Salas, Nieves; Tarakina, Nadezda V. (Journal of Materials Chemistry A)
In situ TEM heating experiments combined with extensive chemical, structural and sorption analysis reveal the nanoscale mechanism of porosity formation in carbonaceous materials obtained directly from molecular precursors.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Modulating between 2e− and 4e− pathways in the oxygen reduction reaction with laser-synthesized iron oxide-grafted nitrogen-doped carbon - Wang, Huize; Jerigova, Maria; Hou, Jing; Tarakina, Nadezda V.; Delacroix, Simon; Lopez Salas, Nieves; Strauss, Volker (Journal of Materials Chemistry A)
Laser patterning of different precursor mixtures allows modulating the selectivity of iron oxide supported on N-doped carbons for ORR electrocatalysis.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

When water becomes an integral part of carbon – combining theory and experiment to understand the zeolite-like water adsorption properties of porous C2N materials - Heske, Julian Joachim; Walczak, Ralf; Epping, Jan D.; Youk, Sol; Sahoo, Sudhir K.; Antonietti, Markus; Kühne, Thomas; Oschatz, Martin (Journal of Materials Chemistry A)
The origin of strong interactions between water molecules and porous C 2 N surfaces is investigated by using a combination of model materials, volumetric physisorption measurements, solid-state NMR spectroscopy, and DFT calculations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

CuII/CuI decorated N-doped carbonaceous electrocatalysts for the oxygen reduction reaction - Kossmann, Janina; Ortíz Sánchez-Manjavacas, María Luz; Zschiesche, Hannes; Tarakina, Nadezda V.; Antonietti, Markus; Albero, Josep; Lopez Salas, Nieves (Journal of Materials Chemistry A)
Copper- and nitrogen-doped carbonaceous materials, obtained by a simple synthetic procedure are highly efficient and fast catalysts for the oxygen reduction reaction. It is shown, that Cu( i ) containing materials perform with faster reaction kinetics.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Understanding additive controlled lithium morphology in lithium metal batteries - Kasse, Robert M.; Geise, Natalie R.; Ko, Jesse S.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Journal of Materials Chemistry A)
Investigation of the mechanisms underlying control of electrodeposited lithium metal morphology using electrolyte additives in lithium metal batteries.

Synergetic modulation of the electronic structure and hydrophilicity of nickel–iron hydroxide for efficient oxygen evolution by UV/ozone treatment - Pan, Ying; Wu, Yanfang; Hsain, H. Alex; Su, Ran; Cazorla, Claudio; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced OER performance of Ni(Fe) hydroxide through UV/ozone treatment.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Assessment of electrocatalytic activity through the lens of three surface area normalization techniques - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei (Journal of Materials Chemistry A)
Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Developing intercalation based anode materials for fluoride-ion batteries: topochemical reduction of Sr2TiO3F2via a hydride based defluorination process - Wissel, Kerstin; Dasgupta, Supratik; Benes, Alexander; Schoch, Roland; Bauer, Matthias; Witte, Ralf; Fortes, Andrew Dominic; Erdem, Emre; Rohrer, Jochen; Clemens, Oliver (Journal of Materials Chemistry A)
Sr2TiO3F2−x, a potential anode material for fluoride ion batteries, is prepared in the charged state via selective low-temperature defluorination.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry